A ten-year overview of cancer genetic family history screening in Georgia’s Latina population - Ramirez Leon, D.; Barber, L. E.; Gabram-Mendola, S.; Snyder, C.; Vadaparampil, S. T.; Fuzzell, L.; McCullough, L. E.; Durham, L.; Guan, Y. (Frontiers in Public Health, 2024)
Background: Population-based cancer genetic family history (FH) screening to identify families at high risk for BRCA-associated cancers has been endorsed by national public health policies. This report aimed to describe the utilization of FH screening services from 2013 to 2022 according to rurality and socioeconomic deprivation among Latinas in Georgia. Methods: Women who attended a medical appointment at participating Georgia Public Health Clinics were invited to complete FH screening. Screening results and participant zip code were reviewed. Area deprivation index (ADI) was measured at the census block group level and dichotomized (more deprived and less deprived). Rurality was measured through Rural-Urban Commuting Area (RUCA) codes and dichotomized (urban and rural). The ADI and RUCA codes were linked to participant data by zip code to characterize FH utilization among the Latina community. Results: Of the 9,330 adult Latinas in Georgia that completed cancer genetic FH screening, 9,066 (97.17%) women screened negative, and 264 (2.83%) screened positive (i.e., FH suggestive of higher risk for carrying BRCA1/2 mutations compared to the general population). Screening completion was higher among Latinas in urban areas (n=7,871) compared to rural areas (n=1,459). Screening completion was also higher in more socially deprived areas (n=5,207) compared to less socially deprived areas (n=4,123). Conclusions: Georgia’s FH screening program reached Latinas across Georgia, particularly those living in urban, socially deprived areas. To ensure equitable cancer genetic screening dissemination, future efforts should prioritize tailored outreach in rural regions and comprehensive evaluations to identify key determinants of screening trends among Georgia’s Latina population.